THE PLACE AND IMPORTANCE OF PEDAGOGY IN THE PRESCHOOL EDUCATION SYSTEM (Universal International Scientific Journal, 2026)
This article discusses the role of pedagogy in the preschool education system, its importance in organizing the educational process, and its role in the comprehensive development of children's personalities. It also analyzes modern pedagogical approaches, taking into account the psychological and pedagogical characteristics of preschool children.
Keywords: preschool education, pedagogy, upbringing, educational process, child development